Analisis Komparasi Daya Dukung Spun Pile dengan Manual, PDA Test dan Allpile: Comparative Analysis of Spun Pile Bearing Capacity with Manual, PDA Test and Allpile - Arga Rumbyarso, Yonas Prima (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
In building planning it is very important to pay attention to the foundation structure such as the Patimban Access Toll Road project located in Patimbant, West Java. This study aims to compare the lateral, axial and settlement bearing capacity of spun pile foundations. This research methodology uses ETABS application to calculate the loading. To calculate the bearing capacity of the foundation using manual methods, namely the Mayerhof, Tomlinson, Reese & Wright method compared with Allpile software and PDA test results. In the analysis of the bearing capacity of the spun pile foundation with a diameter of 100 cm calculated manually, a single pile bearing capacity (Qu) of 9501.238 kN was obtained, a single pile allowable bearing capacity (Qall) of 3800.495 kN and a group pile allowable bearing capacity of 68549.05 kN. The lateral bearing capacity of the foundation using the Broms Method on a single free end pile is 23.181 kN while the pinned end pile is 45.216 kN. Analysis of the settlement that occurs due to axial load on the foundation manually obtained a total settlement value of 0.0232 m with the allowable settlement value limit of 0.1 m. The foundation settlement analysis using the PDA Test results obtained 0.02 m and the foundation settlement analysis using the Allpile program is 0.0687 m